Essays in honor of Aman Ullah - Gonza<U+0301>lez-Rivera, Gloria; Hill, R. Carter; Lee, Tae-Hwy (Emerald, 2016)
Volume 36 of Advances in econometrics recognizes Aman Ullah's significant contributions in many areas of econometrics and celebrates his long productive career. The volume features original papers on the theory and practice of econometrics that is related to the work of Aman Ullah. Topics include nonparametric/semiparametric econometrics; finite sample econometrics; shrinkage methods; information/entropy econometrics; model specification testing; robust inference; panel/spatial models.Advances in Econometrics is a research annual whose editorial policy is to publish original research articles that contain enough details so that economists and econometricians who are not experts in the topics will find them accessible and useful in their research.
Keywords: Ullah, Aman.; Business & Economics -- Economics -- Macroeconomics.; Econometrics.; elektronické knihy; electronic books